Leukemogenic MLL fusion proteins bind across a broad region of the Hox a9 locus, promoting transcription and multiple histone modifications. - Milne, T; Martin, M; Brock, H; Slany, R; Hess, J (2005)
Chromosome translocations involving the mixed lineage leukemia gene MLL are associated with aggressive acute leukemias in both children and adults. Leukemogenic MLL fusion proteins delete the MLL SET domain Lys(4) methyltransferase activity and fuse MLL to 1 of >40 different translocation partners. Some MLL fusion proteins involve nuclear proteins that are transcriptional activators, whereas others have transcriptional activating activity but instead dimerize the truncated MLL molecule. Both types of MLL fusion proteins enforce persistent expression of Hox a9 and Meis1, which is pivotal for leukemogenesis through mechanisms that remain obscure. Here, we show that nuclear and dimerizable forms of MLL bind with a similar pattern to the Hox a9 locus that overlaps the distribution of wild-type MLL and deregulate transcription of three isoforms of Hox a9. Induction of MLL fusion protein activity is associated with increased levels of histone acetylation and Lys(4) methylation at Hox target genes. In addition, the MLL-ENL-ER protein, but not dimerized MLL, also induces dimethylation of histone H3 at Lys(79), suggesting alternative mechanisms for transcriptional activation.